(untitled) - Hurston, Zola Neal (New York, NY, 1995)
Hurston's Novels and Stories presents her nonfiction work, which is perhaps less familiar but no less important than her fiction in the body of black literature. This is the first time the unexpurgated version of her 1942 autobiography, Dust Tracks on the Road, is being published; sections deemed too provocative (dealing with politics, race, and sex) have been restored. Mules and Men (1935) is a collection of African American folklore she gleaned on travels in the South, while Tell My Horse (1938) tenders her personal findings on African-based religion in Jamaica and Haiti
Keywords: Folklorists,Afro-Americans,Afro-American novelists; Biography,Folklore,Biography; United States,20th century